Applicability of Spray Polyurethane Foam Ventilation Guidelines for Do-It-Yourself Application Events. (15th June 2019) - Poppendieck, Dustin; Gong, Mengyan; Ng, Lisa; Dougherty, Brian; Pham, Vu; Zimmerman, Stephen M.
Abstract: Small two-component spray polyurethane foam (SPF) application kits are often applied by Do-It-Yourself (DIY) consumers. The United States Environmental Protection Agency (EPA) publishes a guideline for ventilating a space where SPF is being applied to minimize exposure to mists, vapors, particles and dust. This study sought to assess the applicability of the EPA ventilation guideline in protecting non-application areas of a house from exposure to SPF-associated emissions during a DIY application. Specifically, the research sought to determine if the flame retardant in SPF, Tris(1-chloro-2-propyl)-phosphate (TCPP), migrates outside a temporarily-constructed isolation area during and after a SPF application in the basement of a test home. Tracer decay tests were used to characterize the enhanced ventilation during application. The tracer gas results highlighted the importance of setting up the house internal and external openings to achieve effective isolation and ventilation of the spray area. The DIY spray led to a statistically significant increase in the airborne TCPP concentrations in the basement during the first eight hours after application. However, the basement TCPP concentrations during and immediately after the SPF application were not statistically different from the TCPP concentrations in the basement (associated with the application of SPF during construction) measured four years prior to this application. The data indicate that, for the case tested in this study, following the EPA SPF ventilation guideline protected the rest of the house from elevated TCPP concentrations. However, these results may not hold for higher loading rates, lower airflow rates, leakier isolation enclosures or non-analyzed chemicals. Highlights: Polyethylene sheet enclosures may not completely isolate the SPF application area. EPA ventilation guideline protected the rest of building from TCPP contamination. Following the guideline may not be sufficient for all SPF application scenarios.